Determinanty zakresu praktyki pielęgniarskiej w opiece nad pacjentami nieprzytomnymi = Determinants of the scope of nursing practice in the care of unconscious patients - Ślusarska, Barbara; Słabczyński, Marian; Zarzycka, Danuta; Nowicki, Grzegorz Józef; Deluga, Alina; Zboina, Bożena (Journal of Education, Health and Sport, 2015)
Ślusarska Barbara, Słabczyński Marian, Zarzycka Danuta, Nowicki Grzegorz Józef, Deluga Alina, Zboina Bożena. Determinanty zakresu praktyki pielęgniarskiej w opiece nad pacjentami nieprzytomnymi = Determinants of the scope of nursing practice in the care of unconscious patients. Journal of Education, Health and Sport. 2015;5(11):130-141. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33604 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A130-141 https://pbn.nauka.gov.pl/works/668101 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.09.2015. Revised 05.10.2015. Accepted: 10.11.2015. Determinanty zakresu praktyki pielęgniarskiej w opiece nad pacjentami nieprzytomnymi Determinants of the scope of nursing practice in the care of unconscious patients Barbara Ślusarska1, Marian Słabczyński2, Danuta Zarzycka3, Grzegorz Józef Nowicki1, Alina Deluga1, Bożena Zboina4 1Pracownia Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, UM w Lublinie 2VI Oddział Anestezjologii i Intensywnej Terapii, Szpital Onkologiczny Centrum Onkologii Ziemi Lubelskiej im. św. Jana z Dukli w Lublinie 3Katedra i Zakład Pielęgniarstwa Pediatrycznego, Wydział Nauk o Zdrowiu, UM w Lublinie 4Katedra Pielęgniarstwa, Wydział Pedagogiki i Nauk o Zdrowiu, Wyższa Szkoła Biznesu i Przedsiębiorczości w Ostrowcu Świętokrzyskim Słowa kluczowe: pacjent nieprzytomny, stan funkcji życiowych, różnorodność symptomatologii, praktyka pielęgniarska. Keywords: unconscious patient, state of vital functions, variety of symptomatology, nursing practice. Streszczenie Wstęp. Sprawowanie opieki pielęgniarskiej nad pacjentem nieprzytomnym to złożony i długotrwały proces. Wymaga znajomości uwarunkowań tego stanu oraz samodzielności pielęgniarki w zakresie działań dostosowanych do potrzeb pacjenta nieprzytomnego. Cel. Określenie zakresu symptomów determinujących opiekę wobec pacjentów nieprzytomnych w Oddziale Anestezjologii i Intensywnej Terapii. Materiał i metody. Analizie empirycznej poddano dokumentację szpitalną grupy 101 pacjentów nieprzytomnych, hospitalizowanych w Oddziale Anestezjologii i Intensywnej Terapii (OAIT) w Lublinie w okresie jednego roku. Badania prowadzono metodą retrospektywnej analizy źródłowej dokumentacji medycznej i pielęgniarskiej. Wyniki. Najczęstszą przyczyną stanu nieprzytomności były: urazy (31,68%) oraz zaburzenia świadomości w przebiegu choroby podstawowej (26,73%) i inne czynniki zewnętrzne (21,78%). W analizowanej grupie 55,45% zachowało pełną wydolność oddechową, u 31,68% była zastosowana intubacja, a w przypadku 12,87% założono rurkę tracheostomijną W zakresie funkcji układu moczowego tj. wydalanie moczu u 83,17% osób było kontrolowane poprzez założony cewnik do pęcherza moczowego, natomiast u 16,83% pacjentów zastosowano pieluchomajtki. W zakresie funkcji wydalania stolca u 62,38% stolec był normalny, u 18,81% wystąpiła biegunka i u 18,81% osób wystąpiły zaparcia. Wnioski. Wyniki badań wykazały zróżnicowany stan zdrowia pacjentów nieprzytomnych, który determinuje przedmiot praktyki pielęgniarskiej. Analiza symptomów zarejestrowanych retrospektywnie wśród pacjentów nieprzytomnych wskazuje na dominację obszarów deficytu samoopieki oraz ryzyka powikłań wynikających z braku aktywności ruchowej. Abstract Background. The nursing care of unconscious patients is a complex and lengthy process. It requires knowledge of the conditions of this state and the nurse’s independence in actions adjusted to the needs of the unconscious patient. Purpose. The identification of the scope of the symptoms determining care for unconscious patients at an Anaesthesiology and Intensive Care Department. Material and methods. The hospital documentation on 101 unconscious patients hospitalised in an Anaesthesiology and Intensive Care Department (OAIT) in Lublin over a one-year period was subject to empirical analysis. The research was conducted through the method of the retrospective analysis of source medical and nursing documentation. Results. The most frequent causes of the state of unconsciousness included traumas (31.68%), disorders of consciousness in the course of an underlying disease (26.73%), and other external factors (21.78%). In the analysed group 55.45% retained full respiratory function, 31.68% were intubated, and in the case of 12.87% a tracheostomy tube was used. In terms of urinary system functioning, i.e. urine excretion, this was controlled via a ureteral catheter in 83.17% of cases, and for 16.83% of patients incontinence pads were used. In respect of stool excretion 62.38% of patient had normal stools, 18.81% suffered from diarrhoea and 18.81% from constipation. Conclusions. The examination results indicated varied states of health in unconscious patients which determines the focus of nursing practice. The analysis of symptoms registered retrospectively among the unconscious patients indicates the dominance of the field of self-care deficiency and the risk of complications due to the lack of physical activity.